Interactions between households and industrial sectors in embodied carbon emission networks. (1st December 2020) - Wang, Zhen; Wang, Xiao; Peng, Sha; Ming, Lei; Cui, Can; Niu, Beibei
Abstract: Household activities play an important role in driving industrial carbon emissions. In turn, the industry also affects household emissions via products and value chains. However, previous studies have treated households only as an exogenous driver of industrial carbon emissions; little attention has been paid to interdependencies between households and industrial sectors. Here, we developed a research framework combining semi-closed input-output analysis with network analysis to investigate these linkages. We applied our research framework in Chongqing, China, a city that underwent rapid urbanization from 2007 to 2012. We found that backward linkages (consumption-based accounting) between household and industrial sectors are much stronger than forward linkages (income-based accounting). Therefore, we further investigated mutualistic, controlling, and dependence relationships from the consumption side. The results revealed strong controlling and dependence relationships between households and resource-related, residence-related, and food-related sectors, and more mutualistic relationships between households and industrial sectors over time. In addition, the discrepant results for rural and urban households suggest that urbanization will significantly change the interactions between households and industrial sectors in controlling each other's carbon emissions. Our study helps to elucidate these complex interactions, and the results have implications for developing policies to address rising carbon emissions during urbanization. Graphical abstract: Image 1 Highlights: Households were analyzed as endogenous factors in carbon transfer networks. Power of Pull/Push was used to identify key sectors in backward and forward networks. ENA was applied to reveal mutualistic relationships and interdependencies in networks. Resource-related, residence-related, and food-related supply chains should be controlled.